The Do Gender-Diverse Boards and Audit Committees Enhance Integrated Reporting Quality through ESG Performance? - Tanaya, I Gusti Ayu Agung Tanya Sari Putri; I Made Karya Utama (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2026)
This study examines the influence of gender diversity, audit committee characteristics, and ESG performance on the quality of integrated reporting among firms listed in the ESG Quality 45 Index of IDX KEHATI during the period 2021–2023. The sample comprises 42 firms, yielding a total of 115 firm-year observations. Multiple regression analysis was employed using SPSS Statistics 27 to test the hypotheses. The results indicate that gender diversity and audit committee characteristics do not significantly influence the quality of integrated reporting. In contrast, ESG performance exhibits a positive and significant effect on integrated reporting quality. These findings suggest that companies with stronger ESG performance tend to provide higher-quality integrated reports, reflecting their broader commitment to transparency and accountability. Overall, the study underscores the importance of sustainability and sound corporate governance practices in meeting the information needs of investors and other stakeholders through high-quality integrated reporting. Future research is encouraged to explore alternative measures of the variables and to incorporate moderating or mediating factors to provide a more comprehensive understanding of the determinants of integrated reporting quality.